The InnovAP ecosystem: more than a space for collaboration - Font, Mariluz Llanes (2021)
Abstract Introduction This article presents the result of an investigation that has shown that in the context of the digital age, the public administration needs to transform its management to innovate and seek the generation of new products, services and forms of relationship with citizens, in an agile and transparent, through the use of information and communication technologies and the constant adaptation of its operation and structure to new citizen needs. Principal objective Describe the distinctive characteristics of public innovation, to argue an ecosystem that contributes to its development. Method A qualitative study was chosen in the field of Latin America from 1997 to 2019. The fundamentals were obtained from a documentary research in indexed databases and the review of Cuban strategic documents. Results Among the results is the concretion of the authors' judgments that are reflected in the concept of the public innovation ecosystem, as well as its contextualization through the InnovAP ecosystem. Conclusions Public innovation is more than a space for collaboration, it is made up of interconnected actors, the regulatory environment and the elements that mediate and attribute value to it, all preceded by the establishment of an effective culture of innovation that anticipates the future demands of society to satisfy them.